Salvianolic acid B dry powder inhaler for the treatment of idiopathic pulmonary fibrosis - Peng Lu; Jiawei Li; Chuanxin Liu; Jian Yang; Hui Peng; Zhifeng Xue; Zhidong Liu (Elsevier, 2022)
Idiopathic pulmonary fibrosis (IPF) is a serious and fatal pulmonary inflammatory disease with an increasing incidence worldwide. The drugs nintedanib and pirfenidone, are listed as conditionally recommended drugs in the "Evidence-Based Guidelines for the Diagnosis and Treatment of Idiopathic Pulmonary Fibrosis". However, these two drugs have many adverse reactions in clinical application. Salvianolic acid B (Sal B), a water-soluble component of Salvia miltiorrhiza, could alleviate bleomycin-induced peroxidative stress damage, and prevent or delay the onset of IPF by regulating inflammatory factors and fibrotic cytokines during the disease's progression. However, Sal B is poorly absorbed orally, and patient compliance is poor when administered intravenously. Therefore, there is an urgent need to find a new non-injection route of drug delivery. In this study, Sal B was used as model drug and l-leucine (LL) as excipient to prepare Sal B dry powder inhaler (Sal B-DPI) by spray drying method. Modern preparation evaluation methods were used to assess the quality of Sal B-DPI. Sal B-DPI is promising for the treatment of IPF, according to studies on pulmonary irritation evaluation, in vivo and in vitro pharmacodynamics, metabolomics, pharmacokinetics, and lung tissue distribution.